Mobile Application for Ordering Custom Motorbike Packages at the TWBW Workshop with CRM Implementation - Atsil, Rayhan Alpatih; Samsudin, Samsudin (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The Wild Brain Workshop (TWBW) is a custom culture community in Medan that was founded in 2011. This community started from a custom workshop which then developed into a wider community with a focus on custom motorbikes, music and lifestyle. TWBW, as one of the well-known custom motorbike workshops in the city of Medan, of course gets lots of orders from various custom motorbike lovers. This research was created to create a mobile application for ordering custom motorbike packages by implementing CRM (Customer Relationship Management). The problem formulation in this research is designing an effective mobile application for ordering custom motorbike packages and implementing CRM to improve relationships with customers. The aim of creating this application is so that you can easily view the various custom motorbike packages available, see detailed specifications and prices, and place orders directly through the application. The implementation of CRM in this application is found in the chat feature and customer service menu. By implementing CRM (Customer Relationship Management), it is hoped that TWBW can manage relationships with customers, by utilizing technology to maximize communication and marketing. Through the development of this application, it is hoped that the use of this technology can effectively improve the ordering process.